A capacidade de depressão normal entre mães de bebês em UTI neonatal: uma perspectiva winnicottiana - Carnielli, Flávia Ianzini (2014)
Nowadays depression appears as a major cause of emotional illness and is often associated with sadness, apathy and failure. From this perspective, introspection and withdrawn, which are often characterized as depressive movements, are not taken into account as necessary for elaborating real or imagined losses. From the point of view of DW Winnicott, to deal with the existing psychic challenges, facing situations that break the expectations and idealizations, it is necessary that the individual has surpassed the stage of concern, acquiring the ability to depress which the author relates to emotional maturity. This paper seeks to understand, in the context of motherhood, how the mother's ability to depress associates with the mother's capacity to elaborate the negative aspects regarding the hospitalization of her baby in a Neonatal ICU and, thus, be able to play the role of a good enough mother. For this, a comparative case study was performed between a mother able to develop normal depression, in contrast to other cases (submitted through clinical vignettes) of mothers with difficulties or inability in achieving this process